Annual leave: the case of Taiwan and Malaysia - Ali Hassan Humaid Alhosani, Adnan; Lee, Te Chuan; Ismail, Fadillah; Abdull Rahman, Rabeatul Husna (Penerbit UTHM, 2020)
The definition of annual leave is allowing the organization’s employees to leave the number of hours or days of work within a year without any consequences. Depending on the employer’s policy, different working days may be provided and employees may be required to issue a certain amount of advance notice in advance, which may have to be coordinated with the employer to ensure adequate staffing during the absence of the employee and other requirements may have to be obtained satisfy. Today, most countries have a minimum paid annual leave in accordance with the law. This time off is paid by the company and employees can ask for time for any reason they wish to take the annual leave. Annual leave allows employees to take paid vacations so that they can rest regularly to rest and rejuvenate. Employees on regular vacations are more motivated and perform their work more effectively than those who are not on vacation. Because they have regular breaks, they are less prone to accidents and less likely to be under pressure, which means they can reduce their absence from illness.